Yes means yes : the sufficiency of consent as a justification for the moral acceptability of voluntary prostitution - Ang, Sherin Yue Quin (2018)
Despite the rising importance of sexual consent as perceived by society in recent years, this has yet to be acknowledged and fully extended to the field of prostitution, partly due to its stigmatization as a morally impermissible industry. The moral acceptability of prostitution remains a polarizing debate in feminist philosophy and sexual ethics, with many philosophers perceiving it to be morally unacceptable even when voluntary. However, most existing discussions concentrate on prostitution under coercion and trafficking, and have yet to address the notion of consent in relation to prostitution that is performed voluntarily. This paper will thus discuss and argue for the sufficiency of consent in justifying voluntary prostitution as being morally acceptable, on the basis that sex workers should be able to exercise their individual moral right to self-sovereignty and sexual autonomy. My discussion will focus on consent and the moral acceptability of prostitution, and address the main areas of contention of the sex worker’s right to her sexual autonomy and the legitimacy of prostitution as a labor market. Finally, I will present my own account for a revised definition of consent and voluntary prostitution, asserting that consent is sufficient to justify the moral acceptability of voluntary prostitution.